Write an algebraic expression for the following word phrase.
11.15 less than the product of 42 and x
The word phrase written as an algebraic expression is
16 answers
42x - 11.15
A bagel shop sells bagels by the dozen. The table at the right shows the number of bagels a shop gives per "dozen" ordered. Write an algebraic expression that gives the rule for finding the number of bagels in any number b of dozens.
Bagels
Dozen Number of Bagels
7 84
8 96
9 108
b ___
Number of bagels is
(Type an expression using b as the variable.)
Bagels
Dozen Number of Bagels
7 84
8 96
9 108
b ___
Number of bagels is
(Type an expression using b as the variable.)
Number of Bagels = 12b
3 (x^2 + 5) is an example of which of the following?
Choose the correct answer below.
exponential notation
an algebraic equation
a solution
an algebraic expression
Choose the correct answer below.
exponential notation
an algebraic equation
a solution
an algebraic expression
The correct answer is: an algebraic expression.
Simplify the expression.
(6^2 - 2^3) ÷ 5
(Type an integer or a simplified fraction.)
(6^2 - 2^3) ÷ 5
(Type an integer or a simplified fraction.)
Simplifying the expression, we have:
(6^2 - 2^3) ÷ 5 = (36 - 8) ÷ 5 = 28 ÷ 5 = 5.6
(6^2 - 2^3) ÷ 5 = (36 - 8) ÷ 5 = 28 ÷ 5 = 5.6
Evaluate.
[5/6]^2 =
[5/6]^2 =
To evaluate [5/6]^2, we square the fraction 5/6:
[5/6]^2 = (5/6) * (5/6) = 25/36
Therefore, [5/6]^2 is equal to 25/36.
[5/6]^2 = (5/6) * (5/6) = 25/36
Therefore, [5/6]^2 is equal to 25/36.
Evaluate the expression below for s = 2 and t = 8.
3st^2 - s^2
For s = 2 and t = 8, 3st^2 - s^2 =
3st^2 - s^2
For s = 2 and t = 8, 3st^2 - s^2 =
To evaluate the expression 3st^2 - s^2 for s = 2 and t = 8, we substitute the given values into the expression:
3(2)(8^2) - (2^2)
Simplifying,
= 3(2)(64) - 4
= 384 - 4
= 380
Therefore, when s = 2 and t = 8, the expression 3st^2 - s^2 evaluates to 380.
3(2)(8^2) - (2^2)
Simplifying,
= 3(2)(64) - 4
= 384 - 4
= 380
Therefore, when s = 2 and t = 8, the expression 3st^2 - s^2 evaluates to 380.
Simplify the following expression.
2[(8 - 4)^5 ÷ 8] =
2[(8 - 4)^5 ÷ 8] =
To simplify the expression 2[(8 - 4)^5 ÷ 8], we first simplify the inner expression within the parentheses:
(8 - 4) = 4
So, the expression becomes:
2[4^5 ÷ 8]
Next, we simplify the exponent:
4^5 = 1024
Now the expression becomes:
2[1024 ÷ 8]
Simplifying the division:
1024 ÷ 8 = 128
Finally, we multiply the result by 2:
2 * 128 = 256
Therefore, 2[(8 - 4)^5 ÷ 8] simplifies to 256.
(8 - 4) = 4
So, the expression becomes:
2[4^5 ÷ 8]
Next, we simplify the exponent:
4^5 = 1024
Now the expression becomes:
2[1024 ÷ 8]
Simplifying the division:
1024 ÷ 8 = 128
Finally, we multiply the result by 2:
2 * 128 = 256
Therefore, 2[(8 - 4)^5 ÷ 8] simplifies to 256.
thanks, bot GPT!
You're welcome! I'm glad I could help. If you have any more questions, feel free to ask!
3x - 7 as a word phrase